PENGARUH PEER GROUP HEALTH EDUCATION TERHADAP PERILAKU PERSONAL HYGIENE SISWA SEKOLAH DASAR - Arinil Hidayah; Nurul Hidayah Nasution (Jurnal Education and Development, 2019)
Personal hygiene is one of the basic human needs, personal hygiene or personal hygiene is an effort to maintain one's hygiene and health to obtain physical health and aims to prevent disease. The short-term goal of this study is to determine the effect of Peer Group Health Education on personal hygiene behavior of SDN Hanopan students. The specific target in this study is to examine students' personal hygiene behavior before and after health education is given. This type of research in this study is a pre-experimental study, using one group pre-test and post-test design without a control group. The population is grade 3 students (aged 9-10 years) in Hanopan Public Elementary School, which amounts to 28 people. Analysis of the data used was a Quantitative Analysis using the Wilcoxon Test in two paired samples to test mean differences in pre-post design, with a confidence level of 95% (α ≤ 0.05). The results showed the distribution of respondent's personal hygiene behavior before being given peer group health education showed that it had a mean value of 33.5 approaching the mean value of 35. After being given peer group health education results obtained showed that the average value of 38.07 had exceeded the mean value of 35, this it means that the average personal hygiene behavior of students after being given peer group health education has increased. Wilcoxon test results can be concluded that there is an influence of peer group health education (p_value = 0,000 <α = 0.05) on personal hygiene behavior of students. With the results of this study it is expected to be able to open insight and mindset of health workers to be more active and creative in empowering the community in efforts to improve public health status.